Research on the Measurement of the Development Level of China's Provincial Digital Economy and Its Temporal and Spatial Differentiation Based on the AHP-Entropy Weight Method - Wen Xinzhe (SHS Web of Conferences)
In the wave of global digital transformation, the scale of China's digital economy has continued to expand. However, due to differences in resource endowments, industrial bases, and policy orientations among different provinces, there are significant temporal and spatial disparities in its development level. This has affected the release of the overall effectiveness of the digital economy and regional coordinated development. This study constructs an evaluation system covering 4 first - level dimensions and 11 second - level indicators, including digital infrastructure, digital industry development, digital innovation, and the digital economy environment. By using the AHP - entropy weight method, it measures and analyzes the development level of the digital economy in 31 provinces of China from 2015 to 2024. The results show that: the eastern region has outstanding advantages and has formed an “eastern innovation pole”, while the central, western, and northeastern regions mostly rank in the middle - low echelons; the development of each dimension is unbalanced, with problems such as a disconnection between innovation and industry, large regional differences in infrastructure, and insufficient support from the digital economy environment; the potential for regional collaboration has not been fully exploited, cross - regional data circulation is hindered, industrial collaboration is characterized by “strong points but weak chains”, and the matching degree between computing power supply and demand is low.